THE ART OF PUBLIC SPEECH AND COMPONENT OF SUCCESSFULL SPEECH - Aliyeva Zarnigor (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: Public speaking is a vital skill that plays a key role in education, leadership, business, and social influence. This article explores the essential elements that contribute to the art of public speech and identifies the core components of successful communication in front of an audience. Drawing from communication theory and rhetorical practice, it examines how clarity, confidence, audience awareness, structure, body language, and emotional appeal contribute to speech effectiveness. The article argues that mastering public speaking is not only about verbal delivery, but also about understanding and engaging the audience. Developing this competence can transform a speaker into a persuasive and impactful communicator.